Applied Bioinformatics : An introduction - P M Selzer (Springer, 2018)
This book introduces readers to the basic principles of bioinformatics and the practical application and utilization of computational tools, without assuming any prior background in programming or informatics. It provides a coherent overview of the complex field and focuses on the implementation of online tools, genome databases and software that can benefit scientists and students in the life sciences. Training tutorials with practical bioinformatics exercises and solutions facilitate the understanding and application of such tools and interpretation of results. In addition, a glossary explains terminology that is widely used in the field. This straightforward introduction to applied bioinformatics offers an essential resource for students, as well as scientists seeking to understand the basis of sequencing analysis, functional genomics and protein structure predictions